2007
DOI: 10.1002/joc.1576
|View full text |Cite
|
Sign up to set email alerts
|

Changes in temperature extremes over Italy in the last 44 years

Abstract: Changes in temperature extremes over Italy from 1961 to 2004 were evaluated on the basis of minimum and maximum temperatures measured by 49 synoptic stations uniformly distributed over the country. A set of extreme temperature indices of the Commission for Climatology/Climate Variability and Predictability (CCl/CLIVAR) Working Group on Climate Change Detection was calculated and statistically analysed in order to detect the presence of trends and quantify the variations of the indices for different time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 34 publications
5
63
0
1
Order By: Relevance
“…These increasing trends of hot extremes over the last 20 yr are particularly strong over the Central and Eastern Mediterranean and also in the Black Sea region. This intensification of warming trends is consistent with earlier studies of temperature extremes for Italy that indicate a change point between the end of the 1970s and beginning of the 1980s (Bartolini et al, 2008;Toreti and Desiato, 2008). Potential causes of the enhanced trends are discussed in Sects.…”
Section: Trends In the Indices Of Temperature Extremessupporting
confidence: 90%
See 1 more Smart Citation
“…These increasing trends of hot extremes over the last 20 yr are particularly strong over the Central and Eastern Mediterranean and also in the Black Sea region. This intensification of warming trends is consistent with earlier studies of temperature extremes for Italy that indicate a change point between the end of the 1970s and beginning of the 1980s (Bartolini et al, 2008;Toreti and Desiato, 2008). Potential causes of the enhanced trends are discussed in Sects.…”
Section: Trends In the Indices Of Temperature Extremessupporting
confidence: 90%
“…Moreover, the changes are not always steady or monotonic. Thus, other studies have focused on particular subregions of the Mediterranean such as Spain (Brunet et al, 2007;Rodríguez-Puebla et al, 2010), Italy (Baldi et al, 2006;Bartolini et al, 2008;Toreti and Desiato, 2008), Eastern Mediterranean (Founda et al, 2004;Kostopoulou and Jones, 2005;Kuglitsch et al, 2010), and the Levant and northern parts of Egypt and Libya (Domroes and El-Tantawi, 2005;Zhang et al, 2005;Sensoy et al, 2007;El Kenawy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While analysing temperature extreme indices in northeast Spain, El Kenawy et al (2011) also observed more prevalent changes in hot extremes than in cold extremes. Toreti and Desiato (2008) analysed changes in temperature extremes over Italy and showed a cooling trend until the end of the 1970s followed by a warming trend over the last 25 yr. The most significant results they obtained were related to an increased number of summer days and tropical nights.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most studies have focused on the North Hemisphere, such as North America (Kunkel, 2003;Vincent and Mekis, 2006), Europe (Klein Tank and Können, 2003;Toreti and Desiato, 2008), Asia (Yang et al, 2008;Pal and Al-Tabbaa, 2009;Rahimzadeh et al, 2009;Zhai et al, 2010;Gemmer et al, 2011), possibly due to huge economic losses and social effects arising from climate extremes as well as the data availability. The results of many studies indicate that the frequency and intensity of extreme low temperature events decrease significantly; inversely, distinct increases are found in extreme high temperature events but usually those trends are weaker (Nandintsetseg et al, 2007;Rusticucci and Renom, 2008;Rahimzadeh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%